Evaluating the evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards - Jason J. Kolbe; Jacob D. Ward; C. Mike Norris; John Rodgers; Sydney Wayne; Daniel A. Warner (Evolutionary Ecology, 2026)
Whether phenotypic plasticity facilitates adaptive evolution is a key question in evolutionary ecology. The discovery of limb-length plasticity in two Anolis lizard species led to hypotheses about its role in the Anolis radiation. Yet, whether limb plasticity is realized in nature and has adaptive significance is poorly understood. In this study, we combined a limb-length plasticity experiment, lab-based assays of hatchling behavior, and field-based measures of individual perch-diameter use of hatchling A. sagrei . We compared our findings to previous lab experiments and field studies to better understand the ecological conditions that might elicit limb plasticity and influence the adaptive potential of limb-length in Anolis lizards. Results from our lab experiment did not support limb-length plasticity. Significant limb-length differences due to plasticity were found in some previous experiments but not others. Intriguingly, repeated observations of individual hatchlings at night revealed consistent use of narrow-diameter perches for an island population. In contrast, individual diurnal perch-diameter use in adult A. sagrei was much less uniform. Little evidence exists for adaptive behavior or performance in hatchlings related to limb length and perch diameters. Several aspects of anole behavior and ecology, such as perch preferences and sleep-site use, influence perch-diameter use. Differences among populations in hindlimb length for Bahamian islands often exceed the average plastic response found in lab experiments. Evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards is currently mixed. A better understanding of how perch-diameter use results in biomechanical and developmental cues that influence limb growth is needed. The lack of clear support from lab and field studies urges caution when hypothesizing about the role of limb-length plasticity in the Anolis radiation.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Beat-to-beat blood pressure variability, hippocampal atrophy, and memory impairment in older adults - Trevor Lohman; Isabel Sible; Allison C. Engstrom; Arunima Kapoor; Fatemah Shenasa; Elizabeth Head; Lorena Sordo; John Paul M. Alitin; Aimee Gaubert; Amy Nguyen; Kathleen E. Rodgers; David Bradford; et al. (GeroScience, 2024)
Visit-to-visit blood pressure variability (BPV) predicts age-related hippocampal atrophy, neurodegeneration, and memory decline in older adults. Beat-to-beat BPV may represent a more reliable and efficient tool for prospective risk assessment, but it is unknown whether beat-to-beat BPV is similarly associated with hippocampal neurodegeneration, or with plasma markers of neuroaxonal/neuroglial injury. Independently living older adults without a history of dementia, stroke, or other major neurological disorders were recruited from the community ( N = 104; age = 69.5 ± 6.7 (range 55–89); 63% female). Participants underwent continuous blood pressure monitoring, brain MRI, venipuncture, and cognitive testing over two visits. Hippocampal volumes, plasma neurofilament light, and glial fibrillary acidic protein levels were assessed. Beat-to-beat BPV was quantified as systolic blood pressure average real variability during 7-min of supine continuous blood pressure monitoring. The cross-sectional relationship between beat-to-beat BPV and hippocampal volumes, cognitive domain measures, and plasma biomarkers was assessed using multiple linear regression with adjustment for demographic covariates, vascular risk factors, and average systolic blood pressure. Elevated beat-to-beat BPV was associated with decreased left hippocampal volume ( P = .008), increased plasma concentration of glial fibrillary acidic protein ( P = .006), and decreased memory composite score ( P = .02), independent of age, sex, average systolic blood pressure, total intracranial volume, and vascular risk factor burden. In summary, beat-to-beat BPV is independently associated with decreased left hippocampal volume, increased neuroglial injury, and worse memory ability. Findings are consistent with prior studies examining visit-to-visit BPV and suggest beat-to-beat BPV may be a useful marker of hemodynamic brain injury in older adults.

Prediction of fluid surge in partially-filled clean-bore and transverse baffled tanks of multiple designs under the United Nations Model Regulations - Zhemin Cai; Manudha T. Herath; Luke P. Djukic; Daniel C. Rodgers; Garth M.K. Pearce (Ocean Engineering, 2023)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Insulin-like effects of a physiologic concentration of carnitine on cardiac metabolism - Robert L. Rodgers; Michael E. Christe; George C. Tremblay; John R. Babson; Thomas Daniels (Molecular and Cellular Biochemistry, 2001)